Pathogenesis of severe acute respiratory syndrome - Lau, Yu Lung (Curr Opin Immunol, 2005)
Severe acute respiratory syndrome (SARS) is a zoonotic infectious disease caused by a novel coronavirus (CoV). The tissue tropism of SARS-CoV includes not only the lung, but also the gastrointestinal tract, kidney and liver. Angiotensin-converting enzyme 2 (ACE2), the C-type lectin CD209L (also known L-SIGN), and DC-SIGN bind SARS-CoV, but ACE2 appears to be the key functional receptor for the virus. There is a prominent innate immune response to SARS-CoV infection, including acute-phase proteins, chemokines, inflammatory cytokines and C-type lectins such as mannose-binding lectin, which plays a protective role against SARS. By contrast there may be a lack of type 1 interferon response. Moreover, lymphopenia with decreased numbers of CD4(+) and CD8(+) T cells is common during the acute phase. Convalescent patients have IgG-class neutralizing antibodies that recognize amino acids 441–700 of the spike protein (S protein) as the major epitope.